Current progress of ferroptosis in cardiovascular diseases - Zhang, Jie; Guo, Caixia (Frontiers in Cardiovascular Medicine, 2023)
Ferroptosis, a newly recognized form of nonapoptotic regulated cell death, is characterized by iron-dependent lipid peroxidation. Biological processes, such as iron metabolism, lipid peroxidation, and amino acid metabolism, are involved in the process of ferroptosis. However, the related molecular mechanism of ferroptosis has not yet been completely clarified, and specific and sensitive biomarkers for ferroptosis need to be explored. Recently, studies have revealed that ferroptosis probably causes or exacerbates the progress of cardiovascular diseases, and could be the potential therapeutic target for cardiovascular diseases. In this review, we summarize the molecular mechanisms regulating ferroptosis, inducers or inhibitors of ferroptosis, and the current progresses of ferroptosis in cardiovascular diseases. Furthermore, we discuss the emerging challenges and future perspectives, which may provide novel insights into the treatment of cardiovascular diseases.